Evaluasi Keberhasilan Program Air Minum dan Sanitasi (PAMSIMAS) di Kabupaten Tegal dan Kabupaten Brebes - Kholiq, Abdul (Department of Civil Engineering, Diponegoro University, 2014)
Water supply and sanitationis one of the community-based program launched by the government to hel praise public awareness in water supply and sanitation trouble shooting. This study aims to evaluate the success of the service and performance of community-based water management through PAMSIMAS Program. Goals and objectives to be achieved in this research isto measure people's satisfaction PAMSIMAS program in the village of Karang Mulya and Jejeg in Tegal regency, and village Cilibur and Bentar in Brebes regency with performance assessment regulation of reference by Kepmendagri No. 47, 1999th. Factors community satisfaction was measured by an assessment of the ability of the management of water levels, namely: 1. adequacy of water consumption, 2. continuity of water, 3. water quality, 4. handling technical complaint sand 5. the attitude of the governing body of the society officers. Another goal is to do a SWOT analysis for the formulation of a strategic planin order to be sustainable PAMSIMAS Program infulfillment of clean water.